Mobile Web-Based Campus Life Introduction Information System Using the K-Means Method - mulyadi; Zulfan Khairil Simbolon; Iqbal Panutan (PT. Literasi Teknologi Informatika, 2025)
The introduction of new student campus life (PKKMB) is an annual activity carried out by the Lhokseumawe State Polytechnic campus which aims to prepare new students to go through the transition process to become mature and independent students, as well as accelerate the process of adapting students to a new environment and providing provisions for their success in pursuing education. at University. PKKMB must be carefully planned with several stages in it so that it can be used as a momentum for new students to get accurate information about the education system in higher education, both in the academic and non-academic fields. The small result of the lack of preparation of the activity implementers, sometimes making several stages in this activity, especially in the grouping of new student data, is not optimal, causing several problems such as lack of funding for activities and human errors. The purpose of this research is to build a mobile web-based information system that is useful for making it easier for executors to carry out several stages in this activity, especially in the grouping of new students. So that the purpose of this activity can be maximally accepted both for new students and executors. To collect the data needed in building this system is by conducting interviews with activity executors, and observations. The target of this research is a system website that provides features to facilitate several stages in PKKMB activities. At the stage of grouping new student data, this system uses the K-Means method to cluster new student data with national exam scores and report cards to produce clusters according to the predicate smart, medium, and less, then the results of the clusters will be grouped into 30 groups. according to their respective selection paths.